PENGARUH FEE BASED INCOME DAN INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS PADA INDUSTRI PERBANKAN DI BURSA EFEK INDONESIA - Massie, Gracious Madamba (Katalogis, 2014)
This study aims to identify and analyze the effects of fee based income and intellectual capital(value added capital employed, value added human capital and structural capital value added) on profitability at banking industries in Indonesia Stock Exchange. This study employs 16 samples out of 33 banking industries which have been selected using purposive sampling method. Analysis method used in this study is multiple linier regression. The results shows that: (1) fee based income, value added capital employed, value added human capital, structural capital value added simultaneously perform significant effects on profitability at banking industries in Indonesia Stock Exchange, (2) fee based income performs positive but not significant effect on profitability at banking industries in Indonesia Stock Exchange, (3) value added capital employed performs positive and significant effect on profitability at banking industries in Indonesia Stock Exchange, (4) value added human capital performs positive and significant effect on profitability at banking industries in Indonesia Stock Exchange, (5) structural capital value added performs negative and not significant effect on profitability at banking industries in Indonesia Stock Exchange.